La compensation écologique permet-elle vraiment de tendre vers l’absence de perte nette de biodiversité ? - Brian Padilla; Salomée Gelot; Adrien Guette; Jonathan Carruthers-Jones (Cybergeo, 2024)
Since 2016, French law has pursued the objective of no net loss of biodiversity by requiring projects with impacts on biodiversity to avoid, reduce, and then compensate for these impacts. Offset measures must generate sufficient ecological gains, which presupposes that they are carried out on sites in poor ecological condition. This article analyzes the ecological context in which 1153 offset measures were implemented between 2017 and 2021 in France. Using data on the "potential wilderness of mainland France", we compare the biophysical integrity scores of the selected sites on the one hand and the ecological quality scores, including an index of landscape connectivity around the sites, on the other hand, in relation to national scores. Our results show that 64% of the area of offset sites is located in areas where the biophysical integrity score is above the French median, and 40% is located in spaces where it is above the last quartile. However, the majority of offset sites are found in landscapes with lower ecological quality than the mainland territory. These findings suggest that the strategy for locating compensatory measures does not primarily aim to generate significant ecological gains but rather responds to other economic and land constraints. This raises questions about the effectiveness of offsetting in moving towards no biodiversity net loss.